Critical role of TLR activation in viral replication, persistence, and pathogenicity of Theiler’s virus - Kim, Byung S. (Frontiers in Immunology, 2023)
Infection with Theiler’s murine encephalomyelitis virus (TMEV) results in persistent viral infections in the central nervous system (CNS) and induces chronic inflammatory demyelinating disease in susceptible mice. TMEV infects dendritic cells, macrophages, B cells, and glial cells. The state of TLR activation in the host plays a critical role in initial viral replication and persistence. The further activation of TLRs enhances viral replication and persistence, leading to the pathogenicity of TMEV-induced demyelinating disease. Various cytokines are produced via TLRs and MDA-5 signals coupled with NF-κB activation following TMEV infection. In turn, these signals further amplify TMEV replication and the persistence of virus-infected cells. The signals further elevate cytokine production, promoting the differentiation of pathogenic Th17 responses and preventing cellular apoptosis, which enables viral persistence. Excessive levels of cytokines, particularly IL-6 and IL-1β, facilitate the generation of pathogenic Th17 immune responses to viral antigens and autoantigens, leading to TMEV-induced demyelinating disease. Together with TLR2, these cytokines may prematurely generate functionally deficient FoxP3+CD25- regulatory cells, rapidly converting to Th17 cells. Furthermore, these cytokines inhibit the apoptosis of TMEV-infected cells and the cytolytic function of CD8+ T lymphocytes (CTLs), prolonging the survival of virus-infected cells. The inhibition of apoptosis leads to the persistent activation of NF-B and TLRs, which persistently provides an environment of excessive cytokines and consequently promotes autoimmune responses. Persistent or repeated infections of other viruses such as COVID-19 may result in similar continuous TLR activation and cytokine production, leading to autoimmune diseases.